Formuły metatekstowe podkreślające ważność wprowadzanych treści (na przykładzie encyklik Jana Pawła II) - Gajewska, Urszula (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Among formally and semantically diverse metatexts functioning in encyclicals of John Paul II a large group constitute formulas highlighting importance of introducing content. Recognition by the sender specified information as particularly important is motivated by the evaluation carried out by him, taking into account cognitive and religious criteria. In the analyzed metatextual structures we can distinguish formulas in which signaling importance is the only function, and formulas, in which signaling the importance of introducing content is an additional (accompanying) function, yet the main task of metatexts is naming and accentuating the strategic points of the discourse. Strictly evaluative formulas and persuasively characterized modal formulas, imperative formulas and emotional first-person formulas can be distinguished in both groups. Metatextual indicators signaling the importance of introducing content used by John Paul II are both structures specific to scientific texts, as well as structures peculiar and unusual for them, but characteristic of – for example – catechetical and preaching messages.
Keywords: encyclical; metatext; evaluation; modality; persuasiveness